KEBERAGAMAAN PEDAGANG PASAR SENAKEN KECAMATAN TANAH GROGOT, KABUPATEN PASER - NurNajihah, Niswah; Saputra, Riza (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
Religion fosters diversity and gives rise to religious phenomena in society, which are inseparable from the influence of surrounding realities, including the work environment, such as that of market traders. As spiritual beings, they are obligated to fulfill divine commands. Observing their religious practices offers insight into the emergence of these phenomena. This study employs field research with a descriptive qualitative approach, utilizing a phenomenological perspective on religion. Traders view their efforts as a means of receiving sustenance, yet they believe that sustenance is not solely determined by their endeavors but also by Allah’s decree. Therefore, while conducting business, traders consistently pray and nurture their relationship with Allah. In their daily lives, some traders at Senaken Market leave their stalls to perform obligatory prayers (salat fard) at the market prayer room. During trading hours, they engage in practices such as dhikr (remembrance of Allah), reciting prayers, and giving charity. Additionally, some traders form groups to conduct regular religious activities weekly or during Islamic holidays. These activities help enhance their religious understanding, draw them closer to Allah, and strengthen the bonds of friendship among Senaken Market traders.